2019
DOI: 10.7717/peerj.7283
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale relationship between land use/land cover types and water quality in different pollution source areas in Fuxian Lake Basin

Abstract: The spatial-temporal evolution of land use and land cover (LULC) and its multi-scale impact on the water environment is becoming highly significant in the LULC research field. The current research results show that the more significant scale impact on LULC and water quality in the whole basin and the riparian buffer scale is unclear. A consensus has not been reached about the optimal spatial scale problem in the relationship between the LULC and water quality. The typical lake basin of the Fuxian Lake watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…A decrease in the area of arable land by 69% resulted in a 4-fold reduction of nutrient concentrations (Kowalik et al, 2015). Li et al (2019) found negative correlation between presence of forests and grasses in watershed and values of trophic parameters, total phosphorus and total nitrogen. Walsh & Wepener (2009) when analyzing water quality indexes in Southern Africa showed that in areas with intensive farming river waters fall into water quality classes ranging from poor to moderate.…”
Section: Discussionmentioning
confidence: 80%
“…A decrease in the area of arable land by 69% resulted in a 4-fold reduction of nutrient concentrations (Kowalik et al, 2015). Li et al (2019) found negative correlation between presence of forests and grasses in watershed and values of trophic parameters, total phosphorus and total nitrogen. Walsh & Wepener (2009) when analyzing water quality indexes in Southern Africa showed that in areas with intensive farming river waters fall into water quality classes ranging from poor to moderate.…”
Section: Discussionmentioning
confidence: 80%
“…Province, Fuxian Lake is China's largest deepwater freshwater lake, the first large lake in the source of the Pearl River, and is the Nanpanjiang River system [22]. Its geographical location is 24°21′28″-24°38′00″N and 102°49′12″-102°57′26″E ( Figure 1).…”
Section: General Situation Of the Study Region Located In The Centermentioning
confidence: 99%
“…e industry is dominated by phosphorus chemical industry, building materials, food processing, and aquatic products, of which phosphorus chemical industry is the pillar industry of this area. e land use type of Fuxian Lake Basin has always been dominated by forests and water areas [22]. However, with the improvement of the urbanization level of the basin, human activities have increased disturbance on the natural environment, such phenomena as reclamation of lakes, deforestation, overexploitation of tourism resources, and the rapid increase of functional buildings result in significant change in land coverage types in Fuxian Lake Basin.…”
Section: General Situation Of the Study Region Located In The Centermentioning
confidence: 99%
See 1 more Smart Citation
“…Yang Yuejuan et al, explored the impact of land cover change on the ecological functions of agricultural and pastoral areas in the North [22]. Li Shihu studied the relationship between land cover types and water pollution in the lake basin of Fuxian County under a multi-scale relationship [23]. Li Fei et al, studied the relationship between surface vegetation and heat islands in Hangzhou, China, from 2000 to 2015 [24].…”
Section: Introductionmentioning
confidence: 99%